Understanding Child Neglect Biopsychosocial Perspectives - Sciarrino, Nicole A. (SpringerBriefs in Behavioral Criminology,, 2018)
This concise book reviews the various types of neglect in childhood, providing an operational definition that incorporates existing viewpoints. It describes risk factors for neglect to increase awareness for improved identification, prevention, and treatment of this pervasive problem. This is particularly important as neglect is a growing worldwide issue which receives less attention than more florid forms of abuse. The book aims to facilitate conceptualization and treatment of adult clients who have suffered neglect as well as treatment plans for at risk home environments.